Synthesis and biological evaluation of 1-alkylaminomethyl-1,1-bisphosphonic acids against Trypanosoma cruzi and Toxoplasma gondii - Galaka, Tamila Pavlivna (2019)
As an extension of our project aimed at the search for new chemotherapeutic agents against Chagas disease and toxoplasmosis, several 1,1-bisphosphonates were designed, synthesized and biologically evaluated against Trypanosoma cruzi and Toxoplasma gondii, the etiologic agents of these diseases, respectively. In particular, and based on the antiparasitic activity exhibited by 2-alkylaminoethyl-1,1-bisphosphonates targeting farnesyl diphosphate synthase, a series of linear 2-alkylaminomethyl-1,1-bisphosphonic acids (compounds 21–33), that is, the position of the amino group was one carbon closer to the gem-phosphonate moiety, were evaluated as growth inhibitors against the clinically more relevant dividing form (amastigotes) of T. cruzi. Although all of these compounds resulted to be devoid of antiparasitic activity, these results were valuable for a rigorous SAR study. In addition, unexpectedly, the synthetic designed 2-cycloalkylaminoethyl-1,1-bisphosphonic acids 47–49 were free of antiparasitic activity. Moreover, long chain sulfur-containing 1,1-bisphosphonic acids, such as compounds 54–56, 59, turned out to be nanomolar growth inhibitors of tachyzoites of T. gondii. As many bisphosphonate-containing molecules are FDA-approved drugs for the treatment of bone resorption disorders, their potential nontoxicity makes them good candidates to control American trypanosomiasis and toxoplasmosis.